Intensivist and non-intensivist nurses and their health conducts in the face of professional stress (Research, Society and Development, 2021)
The present study aimed to verify the professional stress factors and the health behaviors of intensive care and non-intensive care nurses from a tertiary health unit in the city of Fortaleza. Cross-sectional, descriptive study, carried out from August to December 2019. The sample consisted of 83 intensive and non-intensive nurses called through the sample for compatibility. An organized survey was used with closed questions about the socioeconomic profile, health behaviors, signs of professional stress and the presence of stressors. The results showed that 64.7% of intensivists used psychoactive substances, among non-intensivists this percentage is only 27.3%. The data reveal that all ICU professionals (100%) said they had some symptom of stress. The presence of stress symptoms among participants who do not work in the ICU reached 93.9%. For non-intensive care nurses, the main factors that trigger stress in the place where their functions are developed are: ‘unsatisfactory environment and absence of inputs’ (56.1%) and ‘absence of professional recognition’ (53%). It was found that 82.3% of ICU participants pointed to 'dissatisfaction with remuneration' as the first stressor, accompanied by 'overload of activities' (70.6%) and 'exhausting work process' (58.8%). It is believed that this study may be favorable, in order for managers to consider the elements that influence the well-being of professional nurses, cooperating in order to implement practices that recover the work state, favoring self-confidence at work.